The Effect of Plyometric and Resistance Training on Increasing The Speed And Explosive Power of The Leg Muscles - Arianda, Eli; Rustiadi, Tri; Yudha Kusuma, Donny Wira (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
Physical conditions in all sports, especially football, need to be trained with good training. The purpose of the study was to analyze the effect of plyometric and resistance training on increasing the speed and explosive power of the leg muscles. This research is an experimental research with a match subject pretest and posttes design. The population is 80 students, the sample is 60 students. Sampling techniquepurposive random sampling. The test instrument in this study was a 30-meter run test and a standing broad jump test. The data analysis technique used Manova. The results showed that Sig. The resulting variables for speed (pre-test), leg muscle explosive power (pre-test), speed (post-test), and leg muscle explosive power (post-test) were 0.614; 0.742; 0.985; and 0.729. Value Sig.=0.002. Sig.=0.002. Sig.=0.031. Sig. = 0.031 because the value of Sig <0.05 then H0 is rejected, so it is concluded that there is an influence between the type of exercise with the speed and explosive power of the leg muscles. Tuckey pre-test and post-test there are differences between plyometric knee tuck jump exercises and resistance squats on increasing speed. As for the plyometric knee tuck jump exercise and the resistance leg press exercise there is no difference, there is no difference between the types of exercises to increase leg muscle explosive power. Conclusion: there was an increase in the speed and explosive power of the leg muscles for each experimental group after being given plyometric and resistance training.